Ultimate resistance of isotropic cylindrically curved steel panels under uniaxial compression. (August 2019) - Manco, Tiago; Martins, João Pedro; Rigueiro, Constança; Simões da Silva, Luís
Abstract: Curved steel panels are increasingly used in several engineering fields yet, design provisions to predict their strength are mostly empirical and with a limited range of application. Consequently, the aim of this paper is to propose expressions for the prediction of the ultimate load of curved panels under uniaxial compression based on a physically robust approach, using semi-analytical methods (SAM). The formulation is based on large deflection theory incorporating initial imperfections and geometric nonlinearity and a first yield criterion applied to the von Mises' stresses is employed. The ultimate load is calculated for a wide parametric variation of geometries considering different amplitudes and patterns of imperfections and boundary conditions. In order to assess the influence of the geometry on the resistance of the curved panels, the curvature parameter, Z, the aspect ratio, α, and the width over thickness, a / h, are varied with the objective to cover most cases of unstiffened curved panels with practical applicability. The influence of these parameters is calculated and validated with the results of the FEM showing good agreement. Highlights: The ultimate resistance of curved panels is established based on semi-analytical methods. Expressions for the elastic non-linear large-displacement behaviour are presented. Accurate expressions to predict the ultimate load are proposed. Validation with FEM simulations is performed for a wide parametric variation.